Jam recenzent, nie policjant. Z perspektywy recenzenta przekładów współczesnej włoskiej literatury w Polsce po 2000 roku - Serkowska, Hanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article is an overview of Polish translations of Italian literature published between 2000 and 2020. The presentation aims to capture the characteristic phenomena of the domestic market of translations from Italian to Polish in times dominated by capitalism and the new media. The author contemplates the role of the reviewer/literary critic in these new conditions, and asks whether reviewers/literary critics can still drive the readers’ choices and receptions, and shape their knowledge and awareness.